Pengaruh Literasi Keuangan, Sikap Keuangan dan Pengelolaan Keuangan Terhadap Kinerja Keuangan pada UMKM Wisata Kuliner Pasar Dhoplang, Kecamatan Slogohimo, Kabupaten Wonogiri - Fatimah Azzahro; D. Ririn Indriastusi (Teewan Journal Solutions, 2026)
This study analyses the influence of financial literacy, financial attitudes, and financial management on the financial performance of MSMEs in the Dhoplang Market Culinary Tourism, Slogohimo District, Wonogiri Regency. Using quantitative methods with primary data, this study applies multiple linear regression analysis, classical assumption tests, as well as t, F, and coefficient of determination (R2) tests. The resulting regression model is Y=−0.665+0.730X1+0.120X2+0.192X3+e. The F-test results indicate that this regression model is statistically significant (p-value=0.000), meaning that the three independent variables—financial literacy, financial attitude, and financial management—simultaneously have a significant impact on financial performance. The coefficient of determination (R2) of 0.971 indicates that 97.1% of the variation in financial performance can be explained by this model. The remaining 2.9% is influenced by factors other than the variables studied. Thus, financial literacy, financial attitude, and financial management have a very large contribution to improving the financial performance of MSMEs in that location.